Oil Content and Fatty Acid Composition in Spring Oilseed Crops - Лихочвор, А. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The objective of researches was to determine the content of glucosinolates and oil in seeds of spring oil crops: spring rape; false flax; mustard white; saperda (indiana) mustard; radish oil; flax oil. In order to assess the suitability of oil for food purposes it is necessary to determined their fatty-acid composition. Besides; the influence of fertilizers on the contents of oil and glucosinolates in seeds of false flax was evaluated. Methods: Determination of quality indices of oil seeds conducted by ISO. Much attention is given to the data of seeds oiliness of spring oilseed crops .It is snown that the highest oil content was flax oil – 51;5%; brown mustard – 45;8% and false flax –- 44;3%. The smallest oil content was in white mustard white – 40;6%. It is shown that the lowest content of glucosinolates is in spring rape (20;4 mmol/g) and false flax (21;5 mmol/g) that’s why the oil because these oil crops used as food. As to the flax oil; the glucosinolates are absent. Study of the influence of fertilizers rates on seed oilnes of fertilizers rates on seeds oiliness of false flax showed; that on higher backgrounds of nutrition the oil contents decreased. Yell; if on the variant without fertilizers it was 46;7%; but on the background of N120R60K120 decreased to 45;7%; or 1%. Discussion: it should be noted; that determination of fatty-acid composition showed that of false flax oil and flax and the best fatty acid composition with predominance of linolenic (50;2% and 57;8%); linoleic (19;3% and 19;8%) and oleic (17;0% and 15;8%) acids. This composition ensures that the oil of false flax and flax can effectively reduce cholesterol levels and has other important medical properties.